2018
DOI: 10.1016/j.cois.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Insect cuticle: a critical determinant of insecticide resistance

Abstract: Intense use of insecticides has resulted in the selection of extreme levels of resistance in insect populations. Therefore understanding the molecular basis of insecticide resistance mechanisms becomes critical. Penetration resistance refers to modifications in the cuticle that will eventually slow down the penetration of insecticide molecules within insects' body. So far, two mechanisms of penetration resistance have been described, the cuticle thickening and the altering of cuticle composition. Cuticular mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
295
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 326 publications
(305 citation statements)
references
References 49 publications
3
295
1
6
Order By: Relevance
“…It is possible that the egg case is much more impermeable to insecticide penetration than other body parts. Cuticle modification in resistant insects is mostly associated with thickening of the cuticle or composition alteration . Because the Res cockroachs presented a CHC profile qualitatively similar to that of the Sus strain, and both of the strains showed highly consistent relative proportions of individual CHC components (Table S2), we consider that the higher amount of CHCs in the Res strain, and possible thickening of the epicuticular layer are major differences between the Res and Sus strains as shown in A. gambiae and Triatoma infestans .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It is possible that the egg case is much more impermeable to insecticide penetration than other body parts. Cuticle modification in resistant insects is mostly associated with thickening of the cuticle or composition alteration . Because the Res cockroachs presented a CHC profile qualitatively similar to that of the Sus strain, and both of the strains showed highly consistent relative proportions of individual CHC components (Table S2), we consider that the higher amount of CHCs in the Res strain, and possible thickening of the epicuticular layer are major differences between the Res and Sus strains as shown in A. gambiae and Triatoma infestans .…”
Section: Discussionmentioning
confidence: 95%
“…Cuticular penetration resistance, which usually involves cuticle thickening, and alteration of cuticular components and the physical structure of cuticle layers, is the least studied mechanism. This slow‐down mechanism has been hypothesized to delay insecticide molecules from reaching their target proteins …”
Section: Introductionmentioning
confidence: 99%
“…Other genetic changes to the thickness or composition of the cuticle may affect insecticide penetration as well. A survey of insecticide resistance in different mosquito species as well as the agricultural pests Heliothis virescens and Myzus persicae showed that many genes related to cuticular functions are up‐regulated in resistant strains of these species . Although these mechanisms have not been functionally tested, it should be mentioned that these different mechanisms could also drive the evolution of insecticide resistance via decreased cuticular penetration and could co‐evolve with adaptation to desiccation stress.…”
Section: Mechanisms Underlying How Climate Change Can Affect Insecticmentioning
confidence: 99%
“…Tyrosinases catalyze the ortho‐hydroxylation of tyrosine to dihydroxy‐phenyl‐alanine (DOPA) and the subsequent two‐electron oxidation to dopaquinone (Rolff et al, ). They are also related to enzymatic browning in fruit and vegetables, pigmentation, and insect physiological processes (Balabanidou, Grigoraki, & Vontas, ; Olmedo et al, ; Xue et al, ).…”
Section: Introductionmentioning
confidence: 99%